2018
DOI: 10.1111/ejn.14275
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve spiking activity associated with locomotion and cortical arousal states in a freely moving rat

Abstract: The vagus nerve serves as a central pathway for communication between the central and peripheral organs. Despite traditional knowledge of vagus nerve functions, detailed neurophysiological dynamics of the vagus nerve in naïve behavior remain to be understood. In this study, we developed a new method to record spiking patterns from the cervical vagus nerve while simultaneously monitoring central and peripheral organ bioelectrical signals in a freely moving rat. When the rats transiently elevated locomotor activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…Although electrical stimulation-evoked responses can be useful in determining the type of activated fibers, these responses do not represent physiological neural signaling. A few research groups have obtained physiological neural recordings from autonomic nerves using extraneural cuff electrodes [31][32][33][34][35] . However, extraneural electrodes lack spatial selectivity, as these electrodes record the compound activity of hundreds to thousands of axons from outside the nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Although electrical stimulation-evoked responses can be useful in determining the type of activated fibers, these responses do not represent physiological neural signaling. A few research groups have obtained physiological neural recordings from autonomic nerves using extraneural cuff electrodes [31][32][33][34][35] . However, extraneural electrodes lack spatial selectivity, as these electrodes record the compound activity of hundreds to thousands of axons from outside the nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Using a new recording method that can monitor the spike pattern of the VN fibres by means of a cuff‐shaped electrode, we revealed that the frequency of VN spikes was higher in novel conditions than in familiar conditions (Shikano et al . ). In addition to this finding, this study showed that there were no prominent differences in the frequency of VN spikes between HF sniffing and RR.…”
Section: Discussionmentioning
confidence: 97%
“…For VN signals, a spike unit was detected when the amplitude of a negative deflection of the extracellularly recorded signals exceeded a threshold of 7-20 µV, which corresponded to five standard deviations from the baseline of the VN signals recorded during quiescent periods in individual animals. Burst spike units detected within a 10 ms bin were regarded as a single spike (Shikano et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations